Q. 75.0( 1 Vote )

Simplify 3x – 5 +

Answer :

We have, 3x – 5 + 23x – 9


Rearranging the terms by putting all variables together and all constants together,


3x – 5 + 23x – 9 = 3x + 23x – 5 – 9


Now, we add the like terms in the expression.


3x + 23x – 5 – 9 = 26x – 14


Observe that 26x = 2 × 13x and –14 = 2 × (–7)


26x – 14 = 2 × 13x + 2 × (-7)


Taking 2 common from both terms, we have


26x – 14 = 2[13x + (-7)]


26x – 14 = 2(13x – 7)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
RELATED QUESTIONS :

The population ofNCERT - Exemplar Mathematics

Health ApplicaNCERT - Exemplar Mathematics

<span lang="EN-USNCERT Mathematics

<span lang="EN-USNCERT Mathematics